Knowledge and Attitude of Nurses on Child Patient Fall Risk Prevention Compliance RSU Saraswati: Pengetahuan dan Sikap Perawat Terhadap Kepatuhan Pencegahan Resiko Jatuh Pasien Anak RSU Saraswati - Nur Hamsar sarmin; Sri Astuti Maharani; Abdul Sila (Politeknik Karya Persada Muna, 2022)
Baground: Hospital patient safety is a system that prevents the occurrence of unexpected events (KTD) due to actions taken or not even carried out by medical and non-medical personnel.. The purpose of this study was to determine the relationship between knowledge and attitudes of nurses on nurse compliance in the implementation of SOP.Method: The design of this study is an observational type using a cross-sectional approach, namely the researcher takes measurements at one time. Observational research is research conducted without giving treatment or manipulation to variables, but only observing. The purpose of cross-sectional research is to describe the phenomenon or relationship of the independent variable with the dependent variable at one time.Results: Result: From the results of statistical tests obtained p value: 0.010, it can be concluded that there is a difference in the proportion of the level of compliance with the implementation of SPO between respondents who have a good attitude and those who have a poor attitude (p value 0.010 <0.05)Conclusions: 0.021 <0.05) means that the better the knowledge of the officers, the better the compliance. There is a significant relationship between attitudes and nurse compliance in the implementation of SOPs: prevention of the risk of falls in pediatric patients Keywords: Knowledge and attitude, compliance, patient safety